Innovation in Material and Production of Rattan Craft in Padang, West Sumatra - Arafat, Bryan (Universitas Putra Indonesia YPTK Padang, 2024)
Rattan is one of the primary forest products in Indonesia, following timber in terms of recognition and utilization. Its unique characteristics, such as flexibility, strength, and durability, make it a preferred raw material for the furniture and handicraft industries. Despite its potential, the development of Indonesia’s rattan industry has been relatively slow. In response, the Indonesian government issued a regulation in 2011 to restrict the export of raw and semi-finished rattan to boost domestic production and value-added processes. According to the Indonesian Rattan Foundation (2010), the annual demand for semi-finished Manau rattan in Indonesia reached 619,538 tons, while the need for finished rattan stood at 533,658 tons. This demand is expected to increase due to government procurement programs supporting domestic production. Indonesia dominates the global rattan market, accounting for approximately 80% of global rattan supply, with production centers located in Kalimantan, Sumatra, Sulawesi, and Papua. West Sumatra is a notable producer, ranking as the sixth-largest rattan-producing province in the country. In Padang, West Sumatra, the rattan processing industry operates as a small and medium enterprise (SME) sector under the city’s Department of Industry, Trade, Mining, and Energy. However, the current production capacity of 48 tons per year in Padang remains insufficient to meet national demand, indicating a significant opportunity for industry expansion and value chain enhancement to strengthen Indonesia’s position as the leading rattan producer globally.